2022
DOI: 10.3390/jmse10030426
|View full text |Cite
|
Sign up to set email alerts
|

From Surface Water to the Deep Sea: A Review on Factors Affecting the Biodegradation of Spilled Oil in Marine Environment

Abstract: Over the past century, the demand for petroleum products has increased rapidly, leading to higher oil extraction, processing and transportation, which result in numerous oil spills in coastal-marine environments. As the spilled oil can negatively affect the coastal-marine ecosystems, its transport and fates captured a significant interest of the scientific community and regulatory agencies. Typically, the environment has natural mechanisms (e.g., photooxidation, biodegradation, evaporation) to weather/degrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 200 publications
0
3
0
Order By: Relevance
“…However, the results of experiments with diatoms exposed to polyaromatic hydrocarbons under controlled conditions using, in some cases, seawater from oil hydrocarbon-contaminated seas [19,[36][37][38]40] have conclusively shown that diatoms' presence enhances the biodegradation of polycyclic aromatic hydrocarbons in contaminated shorelines and seas. Nevertheless, most of the environmental factors that influence microorganisms, mainly eukaryotic microalgae in the sea, also influence the effectiveness of diatoms' biodegradation and bioremediation rate of polyaromatic hydrocarbons in the laboratory, except sea and shoreline energy, such as currents and waves, and seawater pressure [145,146]. Among the environmental parameters, nutrient silicates, nitrogen, phosphorous, and potassium are important for the successful thriving of diatoms in the sea.…”
Section: Environmental Conditions Affecting Diatoms' Petroleum Hydroc...mentioning
confidence: 99%
“…However, the results of experiments with diatoms exposed to polyaromatic hydrocarbons under controlled conditions using, in some cases, seawater from oil hydrocarbon-contaminated seas [19,[36][37][38]40] have conclusively shown that diatoms' presence enhances the biodegradation of polycyclic aromatic hydrocarbons in contaminated shorelines and seas. Nevertheless, most of the environmental factors that influence microorganisms, mainly eukaryotic microalgae in the sea, also influence the effectiveness of diatoms' biodegradation and bioremediation rate of polyaromatic hydrocarbons in the laboratory, except sea and shoreline energy, such as currents and waves, and seawater pressure [145,146]. Among the environmental parameters, nutrient silicates, nitrogen, phosphorous, and potassium are important for the successful thriving of diatoms in the sea.…”
Section: Environmental Conditions Affecting Diatoms' Petroleum Hydroc...mentioning
confidence: 99%
“…Nitrogen (N), phosphorus (P), and potassium (K), are considered as main requirement for effective microbial growth. Their availability may vary according to season of the area and level of water as deep water, have enhanced nutrients but less nutrients are available in surface water (Bacosa et. al.…”
Section: Nutrients Availabilitymentioning
confidence: 99%
“…The first step is the oxidation reaction, which needs an oxygen molecule and is catalyzed by an enzyme; the second is the primary alcohol, which is generated by the oxidation of methyl set; and the last is alcohol, which is then subjected to perpetual processes of oxidation to generate aldehyde, which is frequently converted into fatty acid. Commonly, the oxygen molecule is decreased to water, whereas petroleum hydrocarbons are oxidized to create energy, CO 2 , and cell mass (Bacosa et al, 2022;Brimberry et al, 2023;Kebede et al, 2021;Wang et al, 2011).…”
Section: Bod and Codmentioning
confidence: 99%